2017
DOI: 10.1101/236604
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Uncovering the heterogeneity and temporal complexity of neurodegenerative diseases with Subtype and Stage Inference

Abstract: SummaryThe heterogeneity of neurodegenerative diseases is a key confound to disease understanding and treatment development, as study cohorts typically include multiple phenotypes on distinct disease trajectories. Here we present a new machine learning technique – Subtype and Stage Inference (SuStaIn) – able to uncover data-driven disease phenotypes with distinct temporal progression patterns, from widely available crosssectional patient studies. Results from imaging studies in two neurodegenerative diseases r… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
124
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(160 citation statements)
references
References 41 publications
(61 reference statements)
3
124
0
Order By: Relevance
“…Previous EBM models have shown that in sporadic AD, changes in cognitive abilities, including memory and attention, follow changes in CSF biomarkers, but occur before brain volumetric changes. 16,42 The cognitive tests used in these models have tended to combine several cognitive processes. Here, by including tests for more specific cognitive processes as separate biomarkers, we can look more closely at the sequence of decline in populations where obtaining CSF biomarkers, for example, may be challenging.…”
Section: Discussionmentioning
confidence: 99%
“…Previous EBM models have shown that in sporadic AD, changes in cognitive abilities, including memory and attention, follow changes in CSF biomarkers, but occur before brain volumetric changes. 16,42 The cognitive tests used in these models have tended to combine several cognitive processes. Here, by including tests for more specific cognitive processes as separate biomarkers, we can look more closely at the sequence of decline in populations where obtaining CSF biomarkers, for example, may be challenging.…”
Section: Discussionmentioning
confidence: 99%
“…Thickness of the cerebral cortex decreases with ageing 10,11 . Accelerated cortical thinning is a characteristic feature of cognitive impairment and dementia and may start years before clinical diagnosis 12 . Furthermore, the current understanding is that both obesity and T2DM accelerate brain ageing, and that ageing of the cerebral cortex demonstrates sex‐specific trajectories, with a gradual shift beginning in midlife (around age 50‐59 years) 10,13‐16 …”
Section: Introductionmentioning
confidence: 99%
“…Changes in brain structure continue to provide insight, particularly on the subtypes of disease. For example, the identification of distinct atrophy patterns associated with different rates of disease progression in Alzheimer’s disease and Frontotemporal Dementia [ 9 ]. The SuStaIn model used in this work adds to an understanding of clinical heterogeneity in disease progression by associating differential rates of changes over time with specific patterns of atrophy.…”
Section: Structural Imagingmentioning
confidence: 99%